Analysis of Service Quality, Facilities, And Location on Customer Satisfaction at Jungle Inn Resort, Bukit Lawang, Langkat Regency, North Sumatra - Silvia Rahma Safitri; Annisa Sanny (International Journal of Economics Accounting and Management, 2025)
A resort is a business venture that provides services to meet the recreational, relaxation, and accommodation needs of tourists, whether individuals, families, or groups, by offering complete and diverse facilities. These facilities include comfortable accommodations with various room types, restaurants, recreational areas such as playgrounds, while also creating a relaxed and refreshing atmosphere for the guests. Resort Jungle Inn is one of the businesses operating in this field. Located on the edge of Gunung Leuser National Park, Bukit Lawang offers stunning natural scenery with dense tropical forests and clear rivers. Resort Jungle Inn is facing the problem of a decline in customers and monthly fluctuations in customer numbers. The influence of Service Quality, Facilities, and Location on Customer Satisfaction at Jungle Inn Resort in Bukit Lawang Langkat, North Sumatra, is the subject of this research. data collection through the distribution of questionnaires to 92 respondents. The multiple linear regression model with SPSS processing is used in this research. The research results show that service quality partially has a positive and significant effect, facilities partially have a positive and significant effect, and location partially has a positive and significant effect on customer satisfaction. The Adjusted R Square value of 0.538 indicates that service quality, facilities, and location can contribute fifty-five percent (53.8%) to customer satisfaction, with the remaining forty-five percent (46.2%) potentially attributed to other unexamined variables